Mentoring Youth for Leadership Initiative: Evaluating Impact, Program Practices, and Implementation on High-Risk Youth, United States, 2015-2018 - Stump, Kathryn ([Verlag nicht ermittelbar], 2022)
The aim of this study was to conduct an outcome and process evaluation of the Mentoring Youth for Leadership (MYL) project, which was spearheaded by Leadership Foundations (LF), and utilized an Elements of Effective Practice in Mentoring framework. LF's initiative was designed to reduce youth violence and delinquency, as they strengthen program practices over time. The MYL project served over 3,000 at-risk, high-risk, or underserved youth, their families, and communities, through 26 LF affiliates in 22 states. There were two main objectives: to assess the relations between program practice implementation and youth and match outcomes among mentoring programs in a national network, and to understand the experiences that programs had while embarking on a quality improvement initiative that was focused on improving program practices. Variables include program benchmarks achieved, mentee's school records, relationships with their parents, and staff member's feelings towards their program. Additionally, 16 semi-structured interviews were conducted with 17 MYL program representatives. Mentee's age, gender, race, and ethnicity were also recorded.